DESAIN KEY PERFORMANCE INDICATOR UNTUK PENGUKURAN KINERJA INDUSTRI JASA BERDASARKAN BUDAYA ORGANISASI DENGAN MENGGUNAKAN METODE BSC-AHP (Studi Kasus Hotel Di Semarang) - Nashrullah Setiawan; Andang Farmansyah (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
In 2014 tourist arrivals in Semarang decreased when compared to 2013, which caused the occupancy rate also decreased, this led to increasingly fierce competition among businessmen hospitality. Performance measurement is one way companies look at how big the achievement of the company today. Performance measurement method used is balanced scorecard. This method is able to assess the company not only from the financial aspect, but also from non-financial aspects with reference to the four perspectives that exist. Determination key performance indicator (KPI) in this study consider the vision, mission and values of organizational culture within the company. By using four perspectives in the BSC, there are 12 key performance indicator (KPI) with different interests for each perspective and its KPI based on the weighted analitycal hierarchy process (AHP). The measurement results with the company BSC BSC showed a score of 51.979 included in the final score BSC value of 0, which indicates the value of the company's performance in the Semarang Hotel Grasia sufficient criteria, which means it is still the same as the performance targets set by the company.